The contribution of youth development fund (loans) towards employment creation aiming youth in Zimbabwe from 2009 – 2014: a case of Mashonaland central Province. - Mhuka, Blondie (Midlands State University, 2015)
Youths in Zimbabwe constitute a greater proportion of the total population and are the most marginalised group within the African societies in terms of resource distribution. Therefore, the government of Zimbabwe involves the youths in the economy by introducing the Indigenisation and Economic policy, which was supported by numerous programmes. To address the issue of unemployment the government decided to establish the Youth Development Fund in conjunction with the financial institutions. Against this background, this study sought to establish the contribution of Youth Development Funds (loans) towards employment creation in Mashonaland Central Province, Zimbabwe. The study used a descriptive research design and a combination of purposive and stratified random sampling techniques to select the respondents. Data was collected using questionnaires, interviews and online research triangulated in order to obtain holistic and robust findings. Using descriptive statistics, the results of the study indicated that Youth Development Fund tried to create the employment for the youths but the programme ended up being politicised therefore, the programme regarded as a failure to create the job opportunities for the majority of the youths because the rate of unemployed youths is still high. It managed to create the employment for the elites. In light of the findings, the government of Zimbabwe is advised to monitor and evaluate the funded projects to ensure the feasibility of the project.